The Protective Effects of 18β-Glycyrrhetinic Acid on Helicobacter pylori-Infected Gastric Mucosa in Mongolian Gerbils. (24th February 2016) - Cao, Donghui; Jiang, Jing; You, Lili; Jia, Zhifang; Tsukamoto, Tetsuya; Cai, Hongke; Wang, Shidong; Hou, Zhen; Suo, Yue-er; Cao, Xueyuan
Abstract : 18 β -Glycyrrhetinic acid (GRA), a major component of Glycyrrhiza glabra, is widely used therapeutically in clinic. In this study, the effect of GRA on Helicobacter pylori - ( H. pylori -) infected gastritis was investigated in Mongolian gerbils in vivo . The gerbils were randomly divided into groups: uninfected; H. pylori -infected; H. pylori + antibiotics (clarithromycin, amoxicillin, and esomeprazole); and H. pylori + GRA. The gastric intraluminal pH value, histopathological changes, and the expression levels of inflammation-related cytokines (IL-1 β, TNF- α, COX-2, and iNOS) were investigated. The results showed that, in the H. pylori + GRA group, the intraluminal gastric pH value was lower (2.14 ± 0.08 versus 3.17 ± 0.23, P < 0.05 ), erosion and hyperplasia were alleviated, the infiltration of neutrophils and mononuclear cells was attenuated (P < 0.05 ), and the expression levels of TNF- α, IL-1 β, COX-2, and iNOS were decreased (P < 0.05 ) compared with the H. pylori -infected group. There was no significant difference in results between the H. pylori + GRA group and the H. pylori + antibiotics group. This study indicated that GRA significantly attenuated H. pylori -infected gastritis in gerbils and has the potential to be developed as a new therapeutic drug.